Pemenuhan Hak Perempuan Pasca Cerai Gugat: (Eksistensi SEMA Nomor 2 Tahun 2019 di Pengadilan Agama Nganjuk) - Mochammad Agus Rachmatulloh (SAMAWA, 2022)
The presence of SEMA Number 2 of 2019 regarding the fulfillment of women's rights after a divorce, regarding its application at the Nganjuk Religious Court has not been carried out because there are several factors that hinder its implementation. This study uses the type of empirical legal research. This study uses an socio-legal approach, namely by knowing the facts that occur in the field, the source of the data used is primary through interviews with the Nganjuk Religious Court Judges and secondary data, namely SEMA No. 2 of 2019. The results of the research conducted show that the inhibiting factor in the implementation of SEMA No. 2 of 2019 regarding the fulfillment of women's rights after the divorce was contested, namely the absence of the husband when the divorce was contested, causing the rules not to be implemented, the absence of instructions from the head of the court who had to apply SEMA and the lack of knowledge of the divorced wife about the law, as well as the discrepancy between the Compilation of Islamic Law which requires implement the fulfillment of women's rights after a divorce.